Jesus and Yahweh: The Names Divine – Harold Bloom - Neusner, Jacob (Reviews in religion and theology, 2006)
Book reviewed: Jesus and Yahweh: The Names Divine, Harold Bloom, Riverhead Books 2005 (1-57322-322-0), 238 pp., hb $24.95